IMPACT OF DEEPFAKE TECHNOLOGY ON POLITICAL BEHAVIOR OF YOUTH - Ahmad Shah Bukhari (Policy Research Journal, 2025)
The topic of research study is Impact of Deepfake Technology on Political Behavior of Youth. The purpose of the research was to find out the Impact of Deepfake Technology on Political behavior of Youth. For this study, Propaganda model was applied, this model selected through indepth literature review and propaganda model use there. This research was based on quantitative techniques, while cross sectional sampling was used tocollect the responses. Sample size for this study was 400, which was calculated through statistical formula for sample size. A questionnaire was distributed among the sample from twouniversities in Lahore. The questionnaire was piloted Cronbach's Alpha coefficient of reliability was 625. The data wereanalyzed using descriptive statistics and one sample t-test was used to test the hypothesis. The percentage and frequency of answers were calculated using SPSS (Statistical Package for Social Science). The results of the study shows that negative impact of deepfake technology on political behavior of youth. The result came were positive to accomplish the milestone of the topic chooseby the researcher.